Pretty woman [videorecording (Blu-Ray)] - Lawton, J. F. (Jonathan F.); Gere, Richard, 1949-; Roberts, Julia, 1967-; Bellamy, Ralph, 1904-1991; Alexander, Jason, 1959-; San Giacomo, Laura, 1962-; Elizondo, Hector; Howard, James Newton (Touchstone Home Entertainment, 2009)
Vivian is a spirited, streetwise prostitute working on Hollywood Boulevard. She meets the prince of her dreams in Edward Lewis. Edward is a ruthless and wealthy businessman who does not realize that she could be more than just a girl from the sidewalk. He changes his decision after the first night with the beautiful stranger. Edward hires her for a week of business events in Beverly Hills. Vivian gets the chance to start life over again.